The Role of the Nonspecific Inflammatory Markers in Determining the Anatomic Extent of Venous Thromboembolism. (March 2015) - Bakirci, Eftal Murat; Topcu, Selim; Kalkan, Kamuran; Tanboga, Ibrahim Halil; Borekci, Abdurrezzak; Sevimli, Serdar; Acikel, Mahmut
We aimed to investigate the relationship between the extent of venous thromboembolism (VTE) and nonspecific inflammatory markers such as neutrophil to lymphocyte ratio (NLR) and high-sensitivity C-reactive protein (hs-CRP). We retrospectively enrolled 77 patients with VTE (distal deep vein thrombosis [DVT], n = 19; proximal DVT, n = 32; and pulmonary thromboembolism [PTE], n = 26) and 34 healthy controls. In the performed analysis of variance, the levels of white blood cell, NLR, and hs-CRP were clearly different among the groups (control, distal and proximal DVT, and PTE) ( P < .001). Especially, a significant increase from the control group to the DVT and PTE was observed in the analysis made for NLR. In the performed receiver–operating characteristic curve analysis, area under curve (AUC) = 0.849 and P < .001 were detected for NLR > 1.84. For this value, the sensitivity and specificity were determined as 88.2% and 67.6%, respectively. The NLR is an inexpensive and a readily available marker that may be effective in determining the extent of VTE, and it is useful for risk stratification in patients with VTE.